Statistical ineffective fault analysis of the lightweight authenticated cipher algorithm Saturnin-Short - Wei LI; Chun LIU; Dawu GU; Wenqian SUN; Jianning GAO; Mengyang QIN (Tongxin xuebao)
On the random single byte-oriented fault model and the assumption of ciphertext-only attack, a statistical ineffective fault analysis of the Saturnin-Short cipher was proposed.The analysis combined the statistical distribution with the ineffective analysis, and discussed the difference between intermediate states before and after fault injections.A variety of dual distinguishers was designed, such as the probabilistic symmetric Chi-square-maximum likelihood estimate, and harmonic mean-Hamming weight.It only required at least 1 097 ineffective faults to recover the 256 bit secret key with a success rate of at least 99%.The experimental results show that the proposed distinguishers can not only decrease fault injections, but also reduce the attacking time and complexities.Therefore, the Saturnin-Short cipher cannot resist against the statistical ineffective fault analysis.It provides an important reference for the security analysis of other lightweight authenticated ciphers.